2020
DOI: 10.1039/c9ta13666e
|View full text |Cite
|
Sign up to set email alerts
|

Great improvement in the performance and lifetime of a fuel cell using a highly dense, well-ordered, and cone-shaped Nafion array

Abstract: Great improvement in a fuel cell was achieved by constructing three fast pathways using a highly dense, well-ordered, and cone-shaped Nafion array.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 67 publications
0
60
0
Order By: Relevance
“…However, these H 2 , H 3 , and H 4 peaks were not separated but merged. Meanwhile, the DS was calculated based on the relative integral ratio of H 2,2 ′ to the other protons (H 2 , H 3 ′ ,4 ′, and H 3,4 ). The results showed that the sum of the integral values of H 2 , H 3 ′ ,4 ′, and H 3,4 among the protons of repeating units was initially 12.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these H 2 , H 3 , and H 4 peaks were not separated but merged. Meanwhile, the DS was calculated based on the relative integral ratio of H 2,2 ′ to the other protons (H 2 , H 3 ′ ,4 ′, and H 3,4 ). The results showed that the sum of the integral values of H 2 , H 3 ′ ,4 ′, and H 3,4 among the protons of repeating units was initially 12.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the DS was calculated based on the relative integral ratio of H 2,2 ′ to the other protons (H 2 , H 3 ′ ,4 ′, and H 3,4 ). The results showed that the sum of the integral values of H 2 , H 3 ′ ,4 ′, and H 3,4 among the protons of repeating units was initially 12. After the sulfonation process, the number was found to decrease to 10.2.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there are two established routes to achieve an aligned electrolyte framework, these are, making patterns on the PEM surface [119][120][121][122][123][124] (Fig. 18a) and fabricating ionomer arrays in CLs 125 (Fig. 18b).…”
Section: Building Highways Of Proton and Gas Molecules Through Compon...mentioning
confidence: 99%
“…Besides, CV measurements indicated an increment of the electrochemical active surface area, suggesting an increased exposure of catalytic sites. Regarding the ionomer array structures in CLs, a recent example could be seen in the work by Ning et al, 125 who filled the Nafion emulsion into the aluminium oxide template to prepare a cone-shaped array supported on the bulk membrane and subsequently employed magnetron sputtering to deposit a Pt catalyst into the gaps of the array. The results showed that the MEA with this well-ordered Nafion array as the anode exhibited a Pt mass-specific power which was 2.5 times higher than that given by the ordinary MEA.…”
Section: Building Highways Of Proton and Gas Molecules Through Compon...mentioning
confidence: 99%
“…However, despite the presence of mechanical reinforcement and/or radical scavengers, the lifetime of composite membranes is still limited for long-term fuel cell operation [ 22 , 23 ]. In addition, it is worth noting that even though mechanical reinforcement and radical scavengers are the most frequently used mitigation strategies to increase the durability of PFSA membranes and thus the PEMFC lifetime, other solutions have been proposed in the literature, for instance, new PFSA ionomers with structural features as well as semi-interpenetrating polymer networks have been recently developed to enhance membrane properties [ 24 , 25 ] while a few authors improved the efficiency of the catalyst layers by using a highly dense, well-ordered and cone-shaped Nafion ™ array [ 26 ].…”
Section: Introductionmentioning
confidence: 99%